The death penalty in Algerian legislation - Bouhouche, Hicham (Journal of Human Sciences, 2020)
The Algerian legislator has adopted the death penalty since the dawn of independence, along the lines of many criminal legal systems. However, what is noticeable is that he exaggerated the resort to this punishment, as stipulated in a very large number of crimes, which contradicts his philosophy of punishment that is to reform criminals instead of general deterrence.